Reconstruction of 3D Micro Pore Structure of Coal and Simulation of Its Mechanical Properties - Guang-zhe Deng; Rui Zheng (Advances in Materials Science and Engineering)
This article takes the low permeability coal seam in the coalfield of South Judger Basin in Xinjiang, as a research object. The pore structure characteristics of coal rock mass in low permeability coal seam were analyzed quantitatively using scanning electron microscopy (SEM) through the methods of statistics and digital image analysis. Based on the pore structure parameters and the distribution function of the coal rock mass, a three-dimensional porous cylinder model with different porosity was reconstructed by FLAC3D. The numerical simulation study of reconstructed pore model shows that (1) the porosity and the compressive strength have obvious nonlinear relation and satisfy the negative exponential relation; (2) the porosity significantly affects the stress distribution; with the increase of micro porosity, the stress distribution becomes nonuniform; (3) the compressive failures of different models are mainly shear failures, and the shape of fracture section is related to porosity; (4) the variation of seepage coefficient of the pore reconstruction model is consistent with the development of micro cracks. The micro mechanism of the deformation and failure of coal and the interaction of multiphase flow with porosity are revealed, which provides a theoretical reference for the clean development of the low permeability coal seam.